Numerical Analysis of Target Scattering Characteristics Based on Singularity Expansion Method. (1st March 2023) - Cao, Pei; Li, Pingyang; Wang, Daowei; Lin, Mingzhuang; Wu, Jiuhui
Abstract: Based on the physical meaning of wave equation and Singularity Expansion Method, a numerical solution method is designed to extract the pole distributions of infinite cylinder, sphere and ellipsoid. By analysing the wave equation and boundary conditions of the target scattering characteristics, the extractions of poles of target scattering field are transformed into the solution of Hankel function and its derivative roots. Then, the T-matrix method is improved to make the numerical solution process of roots more accurate and faster. The numerical results are compared with strict analytical solutions and experimental results to fully verify the correctness of the method mentioned in this paper this study provides a basis for understanding the scattering mechanism of surface waves, and also provides a method and idea for solving problems such as acoustic scattering and electromagnetic scattering in engineering practice.